Reduced Hippocampal GABA+ Is Associated With Poorer Episodic Memory in Healthy Older Women: A Pilot Study - Jiménez-Balado, Joan; Ycaza Herrera, Alexandra; Igwe, Kay; Klem, Lynda; Buyukturkoglu, Korhan; Irimia, Andrei; Chen, Liu; Guo, Jia; Brickman, Adam M.; Eich, Teal S. (Frontiers in Behavioral Neuroscience, 2021)
Background: The current pilot study was designed to examine the association between hippocampal γ-aminobutyric acid (GABA+) concentration and episodic memory in older individuals, as well as the impact of two major risk factors for Alzheimer’s disease —female sex and Apolipoprotein ε4 (ApoE ε4) genotype— on this relationship. Methods: Twenty healthy, community dwelling individuals aged 50 to 71 (11 women) took part in the study. Episodic memory was evaluated using a Directed Forgetting task, and GABA+, expressed as the peak ratio of GABA+/creatine concentration, was measured in the right hippocampus using a Mescher-Garwood point-resolved magnetic resonance spectroscopy (MRS) sequence. Multiple linear regression models were used to quantify the relationship between episodic memory, GABA+, ApoE ε4 and sex, controlling for age and education. Results: While GABA+ did not interact with ApoE ε4 carrier status to influence episodic memory (p=0.757), the relationship between GABA+ and episodic memory was moderated by sex: lower GABA predicted worse memory in women such that, for each standard deviation decrease in GABA concentration, memory scores were reduced by 11% (p=0.001). Conclusions: This pilot study suggests that sex, but not ApoE ε4 genotype, moderates the relationship between hippocampal GABA+ and episodic memory, such that women with lower GABA+ concentration show worse memory performance. These findings, which must be interpreted with caution given the small sample size, may serve as a starting point for larger studies using multimodal neuroimaging to understand the contributions of GABA+ metabolism to age-related memory decline.